Conceptualising a credit transfer MOOC initiative for english for technical communication - Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Mohamad Musab, Azmat Ali; Mohd Shafeirul Zaman, Abd Majid (2018)
This paper conceptualizes the notion of diversifying a mainstream course, English for Technical Communication in Universiti Malaysia Pahang to a credit transfer Massive Open Online Course (MOOC), as a full-fledged online course. The changing landscape of educational due to the fourth industrial revolution has noticeably instigated issues confronting higher learning, and so have learning styles and learners’ preferences in learning. Given a wide array of technology choices, learners no longer preferred to be confined with a physical form of classroom, teachers, course books and examinations. Even blended learning course is estimated up to 79 percent of online mode with the remaining in a non-online technique, like the face-to-face. This is yet a solution to issues on conflicts of timetables, as well as in accommodating some learners’ preference of independent learning who could well benefited from a fluid and organic curriculum structure. To approach the study, document analyses on the feasibility of the concept was conducted and feedbacks from the educators and learners of the four semesters enrolment in ‘Becoming Efficient Technical Communicators’ MOOC during trial run rationalized the type of assessments for learning. Resultingly, an innovative mapping of the concept was proposed and justified theoretically and practically. Indeed, this study is timely especially in keeping pace with challenges and opportunities of today’s globalized knowledge economy.